Analysis, Design and Experimentation of a Zero-Voltage Switching Two-Inductor Boost Converter with Integrated Magnetics - Li, Q.; Wolfs, Peter (IEEE, 2006)
A zero-voltage switching (ZVS) two-inductor boost converter with an integrated magnetic structure has been previously proposed to achieve the size and cost reduction in the converter design with discrete magnetics. In the integrated magnetic structure, the five copper windings and the four cores required by the two input inductors, the resonant inductor and the transformer in the original ZVS converter are reduced to three copper windings and one three-limbed core. This paper presents a detailed magnetic analysis of the ZVS two-inductor boost converter with the magnetic integration. The equivalent input and transformer magnetising inductances are established in terms of the reluctances of the individual core limbs and the numbers of the individual windings. This allows the converter with the integrated magnetics to be modelled and analysed using an equivalent design with discrete magnetics. The effects of the leakage reluctances are also considered. The magnetic circuit analysis tool can be also used for any other converters with magnetic integration. In the magnetic design process, the peak and the AC flux densities in the three core limbs are solved explicitly so that saturation and core loss calculation can be easily performed. Finally the theoretical waveforms of a 40-W 1-MHz ZVS converter are also provided to verify the theoretical analysis